Técnicas experimentales aplicadas al condicionamiento clásico de preferencias en el comportamiento del consumidor (2020)
Classical conditioning (CC) is one of the most emblematic developments of experimentalpsychology and psychological science. CC has implied to its area of knowledge: a matterof research, a set of concepts, a methodology, and, finally, a series of technological andinstrumental developments. Like investigation strategy, CC has been used in the study ofa great diversity of processes like perception,learning, memory, and thought. In the sameway,CC is a procedure that has been extended to an important number of applicationfields where it looks for to take part on concrete behavior changes. More specifically, inthe field of consumer behavior, CC are one of the most influential paradigms because itsgreat utility in the explanation on how preferences on goods and services are acquired andmodified. This article pretends introduce to the experimental procedures in CC and CC ofpreferences, in order to indicate their concepts, variables, special phenomena, and researchopportunities.